The emerging role of FK506-binding proteins as cancer biomarkers: a focus on FKBPL. (22nd March 2011) - McKeen, Hayley D.; Brennan, Donal J.; Hegarty, Shauna; Lanigan, Fiona; Jirstrom, Karin; Byrne, Christopher; Yakkundi, Anita; McCarthy, Helen O.; Gallagher, William M.; Robson, Tracy
Abstract : FKBPs (FK506-binding proteins) have long been recognized as key regulators of the response to immunosuppressant drugs and as co-chaperones of steroid receptor complexes. More recently, evidence has emerged suggesting that this diverse protein family may also represent cancer biomarkers owing to their roles in cancer progression and response to treatment. FKBPL (FKBP-like) is a novel FKBP with roles in GR (glucocorticoid receptor), AR (androgen receptor) and ER (oestrogen receptor) signalling. FKBPL binds Hsp90 (heat-shock protein 90) and modulates translocation, transcriptional activation and phosphorylation of these steroid receptors. It has been proposed as a novel prognostic and predictive biomarker, where high levels predict for increased recurrence-free survival in breast cancer patients and enhanced sensitivity to endocrine therapy. Since this protein family has roles in a plethora of signalling pathways, its members represent novel prognostic markers and therapeutic targets for cancer diagnosis and treatment.